2021
DOI: 10.1080/22221751.2021.1872355
|View full text |Cite
|
Sign up to set email alerts
|

Emergence and spread of novel H5N8, H5N5 and H5N1 clade 2.3.4.4 highly pathogenic avian influenza in 2020

Abstract: Analyses of HPAI H5 viruses from poultry outbreaks across a wide Eurasian region since July 2020 including the Russian Federation, Republics of Iraq and Kazakhstan, and recent detections in migratory waterfowl in the Netherlands, revealed undetected maintenance of H5N8, likely in galliform poultry since 2017/18 and both H5N5 and H5N1. All viruses belong to A/H5 clade 2.3.4.4b with closely related HA genes. Heterogeneity in Eurasian H5Nx HPAI emerging variants threatens poultry production, food security and vet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
173
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 177 publications
(183 citation statements)
references
References 7 publications
9
173
0
1
Order By: Relevance
“…On the other hand, cluster G2 had a close genetic relationship with the H5N8 clade 2.3.4.4b viruses that have been identified in the Republic of Iraq, Italy, and England since May 2020 [19], and shared a common ancestor with the viruses detected in Europe during late 2020, suggesting that it was most likely disseminated through overlapping breeding areas between Europe and South Korea during fall 2020. The phylogenetic analysis of the HA gene of the HPAI H5N8 viruses detected in South Korea showed that all the isolates belong to H5 clade 2.3.4.4b and form two distinct genetic groups (G1 and G2), suggesting separate introductions of two genetically distinct H5N8 clade 2.3.4.4 viruses ( Figure 2).…”
Section: Resultsmentioning
confidence: 90%
See 4 more Smart Citations
“…On the other hand, cluster G2 had a close genetic relationship with the H5N8 clade 2.3.4.4b viruses that have been identified in the Republic of Iraq, Italy, and England since May 2020 [19], and shared a common ancestor with the viruses detected in Europe during late 2020, suggesting that it was most likely disseminated through overlapping breeding areas between Europe and South Korea during fall 2020. The phylogenetic analysis of the HA gene of the HPAI H5N8 viruses detected in South Korea showed that all the isolates belong to H5 clade 2.3.4.4b and form two distinct genetic groups (G1 and G2), suggesting separate introductions of two genetically distinct H5N8 clade 2.3.4.4 viruses ( Figure 2).…”
Section: Resultsmentioning
confidence: 90%
“…On the other hand, cluster G2 had a close genetic relationship with the H5N8 clade 2.3.4.4b viruses that have been identified in the Republic of Iraq, Italy, and England since May 2020 [19], and shared a common ancestor with the viruses detected in Europe during late 2020, suggesting that it was most likely disseminated through overlapping breeding areas between Europe and South Korea during fall 2020. Maximum clade credibility (MCC) trees of hemagglutinin gene of H5N8 highly pathogenic avian influenza viruses isolated in South Korea during the winter of 2020-2021 (time shown on the horizontal axis) were inferred using an uncorrelated lognormal distribution relaxed clock in Beast v1.10.4.…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations